دوستی کا قرآنی و نبویﷺ تصور: عصرِ حاضر کے چیلنجز کے تناظر میں ایک تحقیقی جائزہ: The Qur’anic and Prophetic ﷺ Concept of Friendship: A Research Review in the Context of Contemporary Challenges - Dr. Shazia; Hafiza Summan (Al-Amīr Research Journal for Islamic Studies, 2024)
Friendship is one of the most profound human relationships that provides emotional comfort, strengthens social bonds, and contributes to moral development. In Islamic teachings, friendship is not merely a social connection but a spiritual and ethical bond, grounded in faith (īmān) and piety (taqwā). The Qur’an and Sunnah emphasize the importance of choosing righteous companions, as companionship has a direct influence on one’s beliefs and character. This research explores the Qur’anic and Prophetic concept of friendship and critically examines the contemporary challenges that threaten the purity of this relationship, such as materialism, selfishness, sectarianism, social media influence, jealousy, and lack of communication. The study further highlights the guidance provided in the Qur’an, Hadith, and the opinions of Muslim scholars on how to preserve and strengthen friendships in modern times. Findings suggest that Islamic principles of sincerity, patience, forgiveness, benevolence, and preference for others over oneself provide a strong foundation to overcome present-day challenges. The paper concludes that friendship based on Islamic values not only ensures social harmony but also serves as a means of attaining divine pleasure and eternal success. Keywords: Profound, Human Relationships, Comfort, Strengthens, Social Bonds, Materialism, Selfishness, Sectarianism.